Exploring The Nexus Between Students And The Islamic Financial Industry: A Bibliometric Study - Alni Cahya Kamila; Baso Akib; Fadly Yashari Soumena (IECON: International Economics and Business Conference, 2024)
This study explores the relationship between students and the Islamic finance industry through a bibliometric analysis using VOSviewer. The primary objective is to investigate how student involvement contributes to the development of this industry and how educational initiatives align with the practical demands of the Islamic financial market. Utilizing bibliometric data, this research analyzes publication trends, collaboration patterns, and academic contributions from institutions worldwide. Preliminary findings highlight Indonesia as a leading research hub, followed by countries such as Malaysia and the United Kingdom, with key institutions like Airlangga University and the International Islamic University Malaysia playing significant roles. Journals like the *International Journal of Islamic and Middle Eastern Finance and Management* show notable citation impact, indicating a broader academic influence. This study underscores the importance of university-industry collaboration to create a relevant research ecosystem, where students can act as change agents, fostering innovative solutions to meet global challenges in the Islamic finance sector. The findings also suggest potential improvements for Islamic finance curricula and increased academic-institutional partnerships to amplify research impact. This research offers a comprehensive overview of the intellectual dynamics within the field, providing insights for future educational policy and highlighting the value of cross-sector support for advancing Islamic finance.